Analisis dan Perancangan Desain UI/UX pada Website BKPSDM Kabupaten Karawang dengan Metode Design Thinking - Prawira, Kharisma; Lutfiyana, Nur (Justek : Jurnal Sains dan Teknologi, 2025)
The Civil Service and Human Resources Agency (BKPSDM) of Karawang Regency is a Regional Apparatus Organization (OPD) whose duties and functions are to handle civil service administration issues for the State Civil Apparatus (ASN) in Karawang Regency. The administrative issues in question include employee procurement, employee dismissal, employee promotions, and others. Currently, the innovation that has been created and applied is the Website. This website is designed to facilitate the delivery of information regarding Civil Service Administration (ASN) in Karawang Regency. The method used in the Analysis and design uses the design thinking method. This method emphasizes in-depth understanding of users, creative ideation, and prototype iterations that focus on user feedback. This study aims to analyze the UI/UX of the BKPSDM Karawang Regency Website using the Design Thinking method. From the results of the prototype test using the System Usability Scale (SUS) method, the final score was 72, where this figure is acceptable and indicates that the design is marginal, grade B, and good. With this, the Karawang Regency BKPSDM website makes it very possible to improve the quality of UI/UX in its application.